LITTERSIZE DAN MORTALITAS TERNAK BABI DARI PARITAS YANG BERBEDA PADA LOKASI INSTALANSI PENGOLAHAN SAMPAH TERPADU DI KOTA AMBON - Manurung, Ropanti Uli; Souhoka, Demianus Ferdinand; Labetubun, Jusak (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This purpose of this research is to litter size and mortality of pig farming from different parity sows at the integrated waste management installation site in Ambon City. The research method which is conducted is survey method by doing census technique. Variabels that observed are variable treatment in each respons: a) litter size and b) pre-weaning piglet mortality. The results showed that the parity of different parents had no significant effect on litter size. This indicates that the parity factor does not play an important role in influencing the size of the litter born in the population studied. Piglet mortality rates also showed no significant difference among the parity groups. Thus, the parity of sows in this population had no effect on the survival rate of pre-weaning piglets.